The impact of service quality in retail stores on loyalty and repurchase intent through consumer value - Lee, Sin-Bok (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the impact of service quality in large-scale retail stores on customer loyalty and repurchase intention through consumer value (functional value and emotional value). With the recent increase in online shopping and the expansion of contactless services, it has become crucial for offline retail stores to provide differentiated service quality to retain customers and enhance loyalty. The study examines the influence of service quality components (reliability, responsiveness, assurance, empathy, and tangibles) on consumer value and identifies the role of consumer value in shaping customer loyalty and repurchase intention. Based on data from 238 respondents, structural equation modeling (SEM) was utilized for analysis. The results indicate that key elements of service quality positively affect customer loyalty and repurchase intention through functional and emotional value. These findings offer strategic insights for retail stores to strengthen their competitiveness by adopting differentiated service strategies that enhance customers’ emotional value.